Non-destructive diagnosis of wiring networks using time domain reflectometry and an improved black hole algorithm. Issue 3 (3rd July 2017) - Smail, M. K.; Bouchekara, H. R. E. H.; Pichon, L.; Boudjefdjouf, H.; Amloune, A.; Lacheheb, Z.
Abstract: The aim of this paper is to propose a new efficient and reliable approach for the diagnosis of wiring networks using Time Domain Reflectometry (TDR) and an Improved Black Hole (IBH) optimisation algorithm. A forward model based on RLCG parameters and Finite Difference Time Domain (FDTD) method is developed to simulate the TDR response for a given wiring network. The IBH algorithm is used to solve the inverse problem in order to detect, characterise and localise defects in wiring networks. Experimental studies are performed to show that the proposed approach can be implemented for the diagnosis of real-world systems. The results presented here demonstrate that the proposed approach using TDR and IBH is an efficient and reliable diagnosis approach for wiring networks.